Penyediaan peralatan sokongan untuk persekitaran pengajaran dan pembelajaran pengaturcaraan C melalui peningkatan penggunaan hiperbuku dan sistem pengurusan Kursus (CMS) - Syarilla Iryani Ahmad Saany
The influence of Information and Communication Technology (lCT) has been enormous in plenty of fields including the education field. ICT helps by enhancing the teaching and learning process and also garnishing interest among students towards learning. The step towards computerization will also provide assistance to instructors in the area of courses' management. The use of Hyperbook concept in the teaching and learning of C Programming has previously been developed in Universiti Kebangsaan Malaysia (UKM). The Hyperbook acts as notes or reference, which in turns enhances the CAPL system (Computer Aided Programming Learning). The CAPL system was also developed in UKM as a computerized learning system where students could access information about the course syllabus, related exercises, mail and messaging facilities; also known as motd (i.e. from lecturers to students). The development of Hyperbook was based on the traditional book learning format and it could only be accessed via CAPL system. Along the application developed for students, an application has also been developed for the usage of instructors known as CMS (Course Management System). CMS helps instructors to properly organize and manage courses. Starting with the registration of students, assessment of assignments and also assignment grading, all can be executed by CMS. The integration of the two packages, Hyperbook and CMS, will provide a total solution system which will further enhance the effectiveness and efficiency of the teaching and learning processes. Upgrading has been done to both packages so that the application can be adapted in the learning of basics topics in C Programming as well as supporting the smoothness of management process on the part of the instructors. The upgraded packages will also help in the management process for the instructors. For the student module, the Hyperbook has been enhanced so that it will not only used as a reference but also useful for doing exercises, mailing capabilities, facilities for upgrading exercises or notes and also facilities for receiving assignments from instructors. The instructor module on the other hand, will be furnished with the capabilities of receiving, marking and grading programming assignments. The end result will be a package that can be adapted in the teaching and learning process of C Programming thus making a leap from traditional learning process to digital.